2017
DOI: 10.20944/preprints201701.0089.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coaxial MoS<sub>2</sub>@carbon Hybrid Fibers: A Low-Cost Anode Material for High-Performance Li-Ion Batteries

Abstract: Abstract:A low-cost bio-mass-derived carbon substrate has been employed to synthesize MoS 2 @carbon composites through a hydrothermal method. Carbon fibers derived from natural cotton provide a three-dimensional and open framework for the uniform growth of MoS 2 nanosheets, thus hierarchically constructing coaxial architecture. The unique structure could synergistically benefit fast Li-ion and electron transport from the conductive carbon scaffold and porous MoS 2 nanostructures. As a result, the MoS 2 @carbon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…7,24 As shown in Figure 3c, S 2p exhibits two contributions, 2p 3/2 and 2p 1/2 , located at ∼163.3 and ∼164.5 eV, respectively. 16,36,37 In Figure 3d, it can be observed that the C 1s peaks of CCS are composed of four components: C sp 2 (∼285.1 eV), C sp 3 (∼286.0 eV), C−O bonds (∼288.0 eV), and π− π* (∼290.1 eV). 12,22,38 According to the results, the CCS shows a high degree of graphitization.…”
Section: Resultsmentioning
confidence: 99%
“…7,24 As shown in Figure 3c, S 2p exhibits two contributions, 2p 3/2 and 2p 1/2 , located at ∼163.3 and ∼164.5 eV, respectively. 16,36,37 In Figure 3d, it can be observed that the C 1s peaks of CCS are composed of four components: C sp 2 (∼285.1 eV), C sp 3 (∼286.0 eV), C−O bonds (∼288.0 eV), and π− π* (∼290.1 eV). 12,22,38 According to the results, the CCS shows a high degree of graphitization.…”
Section: Resultsmentioning
confidence: 99%
“…However, the poor electrical conductivity, low cycling stability, and high agglomerate risk remain the major drawbacks of bulk MoS 2 . To overcome these problems, numerous studies of growth of MoS 2 on different conductive substrate or supports, such carbon paper [12][13][14][15], graphite [12,13], 1D carbon nanotubes (CNTs) [10,11,14,[16][17][18][19], 3D nanocarbon [20], carbon nanofiber [21], or graphene [10,14,22,23], were conducted to improve their electrochemical performance and stability. Well reversible specific capacity as high as 1,290 mAh•g -1 were reported for nanostructured MoS 2 -graphene anodes [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue covers seven research articles, including four papers on Li-ion batteries, one paper on Li-sulfur batteries, one paper on Li-ion capacitors and one paper on asymmetric supercapacitors. With regard to the anode materials for Li-ion batteries, Wang et al developed a low-cost yet high-performance anode material of MoS 2 /bio-mass-derived carbon composite that can deliver a specific capacity of 820 mAh g −1 [ 12 ], while Jeong et al reported a binder-free anode of mesoporous carbon nanotube–carbon nanofiber prepared by electrospinning [ 13 ]. In the field of cathode materials for Li-ion batteries, Wang et al explored a three-dimensional V 2 O 5 hollow structure through a novel solvothermal synthesis strategy, and comparesd the Li-ion storage performance of V 2 O 5 annealed at different temperatures [ 14 ].…”
Section: Introductionmentioning
confidence: 99%